Multi Band Metamaterials Absorber for Stealth Applications (Law, State and Telecommunications Review, 2019)
Purpose ”“ This paper presents a simulation study using CST microwave studio computer software.Methodology/approach/design ”“ A simple structure based on metamaterial are used to construct a perfect metamaterial absorber. It is made of just one uncompleted square patch copper placed on top of dielectric layer to separate it from a copper ground plate.Findings ”“ This design provides four perfect absorption regions with absorption peaks of an average of 93%. The characteristic study of parameters such as copper dimensions and dielectric properties led to an expected result in the synthesis of resonant frequency.Practical implications ”“ The multi-band absorption can be used in energy harvesting applications, protection from the effects of electromagnetic waves, radar stealth technology and thermal imaging. Moreover, the experimental results show good agreement with CST simulation.